Correlations between ejecta boulder spatial density of small lunar craters and the crater age. (1st November 2018) - Li, Yuan; Basilevsky, A.T.; Xie, Minggang; Ip, Wing-Huen
Abstract: This work explores the quantitative correlation between the ejecta boulder number density and crater age for seven craters from ∼200 m to 1 km in diameter. Using the selected set of LRO NAC images with resolution ∼0.5 m/pixel we mapped and counted the ejected boulders larger than 3 m across inside the one-crater-radius-wide concentric annulus (or its part) from crater rim, for craters South Ray, Unnamed A, Unnamed B, Cone, North Ray, Unnamed D and Camelot. This study partly repeats the work of Basilevsky et al. (2013, 2015b) on the study of spatial density of boulders of small lunar craters of known formation age, but based on the larger counting areas, thus the larger numbers of ejecta boulders were counted. The results from our study are certainly statistically more reliable. This study does not only confirm the results of Basilevsky et al. (2013, 2015b) that spatial densities of boulders generally decrease with crater age, but also find the mare craters are generally more rockiness than highland craters if given similar formation ages, which is interpreted as the effect of the higher mechanical strength of mare rocks (basalts) comparing to that of highland rocks (fragmental breccias). We also found the quantitative relations between boulder spatial density (>3 m) and the age of mare craters and highland craters, respectively. The applicability tests show that these relations are only suitable for craters smaller than 1 km in size. This is interpreted as the excavation of less fragmented bedrocks due to deeper excavation depth for large size craters (>1 km), resulting in a different boulder size distribution in comparison to that for craters < 1 km. This study improves the understanding of the boulder size distribution for crater <1 km in size, and provides a new perspective on the crater age determination using boulder spatial density. Highlights: Spatial density of >3 m ejecta boulders was studied for 10 small size lunar craters. The boulder density is higher in maria where bedrock is mechanically stronger. The correlation of boulder spatial densities and crater age was quantified. Most of the boulders for the studied craters are destroyed in the first 115–130 Ma. The boulder decreased trend is steeper in maria indicates loose mechanical strength.